Defining the elite: normative values for scat major components in healthy elite athletes. Issue 11 (25th May 2017) - Moreau, William J; Walden, Taylor; Nabhan, Dustin
Abstract : Objective: Describe normative baseline SCAT 2 and 3 (SCAT) performance in elite athletes. Design: Retrospective cohort. Setting: United States Olympic Committee Sports Medicine Clinics. Participants: Six hundred and forty-one SCAT baseline evaluations were performed on a population of 565 elite athletes (291 women and 350 men, mean age 24.9±5.2 years) representing 23 Summer and Winter Olympic sports as part of a multimodal concussion management program. Intervention: No intervention was applied. The SCAT evaluations were administered as a component of baseline testing on healthy athletes. Main Outcome Measurements: Baseline SCAT performance on major components is described. T-tests were used to compare differences in baseline performance by sex. Results: During baseline evaluation elite athletes reported a mean of 2.1 (1.8–2.4) symptoms with average symptom severity scores of 3.4 (3.0–3.9). Mean scores on SCAT 3 components in this population were; orientation 4.9 (4.8–4.9), immediate memory 14.5 (14.4–14.5), concentration 3.9 (3.8–4.0), tandem gait 11.7 (11.4–12.0), delayed recall 3.7 (3.6–3.8), balance 2.83 (2.2–3.4), SAC total 26.9 (26.8–27.1). This population reported historys of 1.19 (1.0–1.4) previous concussions. Females reported significantly more symptoms (3.9 vs 3.0, P=0.04), and scored significantly higher on the orientation (4.9 vs. 4.8, P=0.004), immediate memory (14.6 vs. 14.4, P=0.003), concentration (4.1 vs 3.8, P=0.0013) SAC total score (27.3 vs. 26.6, P<0.01) Conclusions: Population specific normative values for baseline SCAT performance in a population of elite athletes are presented in this case series. Clinical relevance: Clinicians are encouraged to reference population specific normative values when interpreting SCAT performance. Acknowledgements: None. Competing interests: None.